2017
DOI: 10.4414/smw.2017.14567
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability and effectiveness of integrated care for COPD patients: a mixed methods evaluation of a pilot community-based programme

Abstract: The evaluation demonstrated the feasibility and acceptability of the programme and confirmed the relevance of mixed method process evaluation to adjust and improve programme implementation. The introduction of multidisciplinary teams in a context characterised by fragmentation of care was identified as the main challenge in the programme implementation and could not be achieved as expected. Despite this area for improvement, patients' feedback and early effectiveness results confirmed the benefits of COPD inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Their level of involvement varied, but nurses engaged rather actively and performed patient assessments, developed and reviewed care plans, coached staff, took over patient education and shared responsibilities with GPs (19, 21, 22, 30-33, 35-39, 43, 44, 47, 49). Other HCPs with active roles included pharmacists, physiotherapists and community health workers who provided patient education on profession-speci c care (31)(32)(33)38). In a Canadian project, the research staff was engaged actively and performed pharmacological consultations and medication reviews (29).…”
Section: Education and Knowledge Transfermentioning
confidence: 99%
See 3 more Smart Citations
“…Their level of involvement varied, but nurses engaged rather actively and performed patient assessments, developed and reviewed care plans, coached staff, took over patient education and shared responsibilities with GPs (19, 21, 22, 30-33, 35-39, 43, 44, 47, 49). Other HCPs with active roles included pharmacists, physiotherapists and community health workers who provided patient education on profession-speci c care (31)(32)(33)38). In a Canadian project, the research staff was engaged actively and performed pharmacological consultations and medication reviews (29).…”
Section: Education and Knowledge Transfermentioning
confidence: 99%
“…Authors reported on the respective condition's burden on healthcare facilities or system resources such as high consultation rates (23,24,28) or costs (29)(30)(31)(32)(33)(34). Furthermore, projects presented that the health condition of interest is a leading cause of morbidity, hospitalizations and death (30)(31)(32)(33)(35)(36)(37)(38)(39)(40). The current organization of care and its coordination was often considered suboptimal or even outdated for the speci c health condition.…”
Section: Rationale For Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research in relation to integrated respiratory care has identified some promising results in terms of integration and admission avoidance [4][5][6] but in general the results have been mixed. [7][8][9] Despite the policy prioritisation associated with integrated care, research and evaluations have not produced clear evidence of effectiveness. 3 10-14 Studies have shown how tensions between the professional cultures of different organisations can impede integration.…”
Section: Introductionmentioning
confidence: 99%